2013
DOI: 10.1159/000354545
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Special Radiological Signs on Routinely Obtained Supine Anteroposterior Chest Radiographs for the Early Recognition of Neonatal Pneumothorax

Abstract: Background: Bedside chest radiographs used for the confirmation of diagnosis of pneumothorax in the neonatal intensive care unit (NICU) are routinely obtained in the supine position. However, pneumothoraces may not appear in the classically described forms on these radiographs, resulting in a delayed diagnosis. Objective: To assess the utility of special radiological signs in the neonatal population for the early recognition of pneumothorax. Methods: A case-control study was conducted at a level III referral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…To our knowledge, no tested method has achieved 100% accuracy. Accuracy in our study is likely to be <100% because diagnosing neonatal pneumothorax can be difficult regardless of the media used to review the image.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, no tested method has achieved 100% accuracy. Accuracy in our study is likely to be <100% because diagnosing neonatal pneumothorax can be difficult regardless of the media used to review the image.…”
Section: Discussionmentioning
confidence: 94%
“…Per Jiang et al, (2015), close monitoring of respiratory status is indicated for neonates who received ventilation support at birth. Intensive care is required for neonates who received delivery room intubation with or without CPR, especially during the first week of life [5].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, aggressive resuscitation through positive pressure ventilation (PPV) and continuous positive airway pressure (CPAP) is a known risk factor for pulmonary air leak and can result in dissection of air into the pleural space or mediastinum, known respectively as pneumothorax (PTX) or pneumomediastinum (PM), as confirmed through chest radiographs (CXR) [5,6]. Most cases of air leak occur in neonates with underlying lung disease, especially if mechanical ventilation is required [7].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation ranges from asymptomatic to severe progressive respiratory distress [ 102 ] and, in case of tension pneumothorax, hemodynamic compromise [ 109 ]. Physical examination may reveal tracheal deviation, asymmetrical chest rise, diminished breath sounds over the affected side, and muffled or shifted heart sounds [ 109 ]. Diagnosis is usually made by radiography [ 109 ].…”
Section: Complications: Air Leaks and Pulmonary Hemorrhagementioning
confidence: 99%
“…Physical examination may reveal tracheal deviation, asymmetrical chest rise, diminished breath sounds over the affected side, and muffled or shifted heart sounds [ 109 ]. Diagnosis is usually made by radiography [ 109 ]. However, in neonates, the classic appearance may be more difficult to recognize.…”
Section: Complications: Air Leaks and Pulmonary Hemorrhagementioning
confidence: 99%